Faktor-Faktor Yang Mempengaruhi Kesehatan Mental Pada Remaja Sekolah Menengah Pertama (SMP) Swasta “X” Di Wilayah Uptd Puskesmas Melayu Kota Piring - Evike Astriyani; Ennimay Ennimay; Rizki Sari Utami Muchtar (STIKes Ibnu Sina Ajibarang, 2025)
The issue of mental health has been widely discussed in recent years. In general, mental health is the state of an individual who is aware of their own ability to cope with the normal stresses of life, therefore mental health is very important, especially among teenagers, because during adolescence there are many changes. psychosocial such as cognitive, psychological, social and biological. This development is a crisis event for teenagers which can cause impacts such as anxiety, stress and depression. The aim of this research is to determine the factors that influence mental health in teenagers at private junior high school (SMP)